Experimenting with Farmers' Capacity and Social Institutions Building for ensuring Village Level Seed Sufficiency: A Case of Chickpea (Cicer arietinum L) in India - Dubey, Shantanu Kumar; Singh, S. K.; Nigam, S. N.; Sah, Uma; Ali , M.; Yadav, A. S. (Indian Journal of Extension Education, 2015)
Building farmers' capacity to experiment with the recommended technologies and at the same time facilitating them for  institutionalizing their efforts requires constant validation, consolidation and upscaling. An action research was  conducted to empirically probe how the recommended and improved seed varieties may appear if looked with farmers'  lens and how to a large extent the farmers' preferred varieties may reach, while using the interventions of institutional  backstopping, capacity building, hand holding and enabling. Chickpea is a major pulse crop of India. However, its  productivity is restricted around 896 kg/ha, over the past several decades. Local landraces and varietal admixture are  influencing the chickpea cultivation in the country. One of the major reasons for low productivity of chickpea is the non availability of quality seed of improved varieties among the farmers. In the present paper, the experiences of farmer participatory chickpea seed production in districts of Fatehpur and Kanpur Dehat in Uttar Pradesh state of India have been  shared. Through farmer-participatory varietal selection trials, farmers identified DCP 92-3 and JG 16 varieties, as their  preferred choices. These varieties were preferred because of its high yield, attractive seed size, seed color, better taste and  cooking quality. Farmers were organized to form cooperative societies to undertake seed production, processing and  marketing at the local level. They were also linked with the public sector seed producing agencies to participate in the  formal seed production program. The B:C ratio of seed production of DCP 92-3 and JG 16 variety was 2.94 and 3.18 as  compared to 2.15 of the local chickpea variety sold as grain. Village level seed production not only addressed the issue of  shortage of quality seeds but also brought higher incomes to farmers leading to their improved livelihood.
Keywords: Participatory approach; Institutional linkages; Seed delivery; Farmer association